2016
DOI: 10.1523/jneurosci.4100-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Predicting “When” in Discourse Engages the Human Dorsal Auditory Stream: An fMRI Study Using Naturalistic Stories

Abstract: The hierarchical organization of human cortical circuits integrates information across different timescales via temporal receptive windows, which increase in length from lower to higher levels of the cortical hierarchy (Hasson et al., 2015). A recent neurobiological model of higher-order language processing (Bornkessel-Schlesewsky et al., 2015) posits that temporal receptive windows in the dorsal auditory stream provide the basis for a hierarchically organized predictive coding architecture (Friston and Kiebel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 68 publications
(104 reference statements)
0
30
0
Order By: Relevance
“…Predictions modulate auditory evoked responses in an area specific manner, involve both the ventral and dorsal pathways (Kandylaki et al, 2016; Sohoglu and Chait, 2016), and affect both feedforward and feedback connections (Auksztulewicz and Friston, 2016; Chennu et al, 2016). While an informative visual context facilitates the correction of predictions about expected speech using incoming multisensory evidence, we can only speculate about a direct link between the reported effects and predictive processes.…”
Section: Discussionmentioning
confidence: 99%
“…Predictions modulate auditory evoked responses in an area specific manner, involve both the ventral and dorsal pathways (Kandylaki et al, 2016; Sohoglu and Chait, 2016), and affect both feedforward and feedback connections (Auksztulewicz and Friston, 2016; Chennu et al, 2016). While an informative visual context facilitates the correction of predictions about expected speech using incoming multisensory evidence, we can only speculate about a direct link between the reported effects and predictive processes.…”
Section: Discussionmentioning
confidence: 99%
“…To fill this gap, recent language research has relied more on an ecological approach in which complex, naturalistic, real-life stimuli are employed to unveil the neural processes underlying speech comprehension. For example, stories have been frequently employed (Beeman et al, 2000;Ferstl, Rinck, & Cramon, 2005;Hartung, Hagoort, & Willems, 2017;Haupt, Schlesewsky, Roehm, Friederici, & Bornkessel-Schlesewsky, 2008;Kandylaki et al, 2016Kandylaki et al, , 2017 in both first and second language studies (Hsu, Jacobs, & Conrad, 2015). The degree of naturalness and complexity varies; for example, Haupt et al (2008) used very short stories and engaged participants in a comprehension task, while Kandylaki and colleagues employed longer texts in the absence of a specific task (Kandylaki et al, 2017).…”
Section: "Shifting": From Sentences To Narrativesmentioning
confidence: 99%
“…Besides being closer to reallife story telling, stories also allow tackling mechanisms such as the processing of information spanning over longer time scalesthat short phrases would not allow identifying: As stories usually follow a coherent evolution, predictions on what is going to happen next in the narrative can be done based on the evolving context. This process has been explored in an fMRI study by Kandylaki and colleagues, who showed that this type of prediction engages the dorsal auditory stream, comparable with a hierarchical predictive coding architecture (Kandylaki et al, 2016; see also Willems, Frank, Nijhof, Hagoort, & Van Den Bosch, 2016). Such long-range effects could not be detected in classical experimental set-ups that would also not allow marking sustained effects that arise in an evolving story line which generates expectations (e.g.…”
Section: "Shifting": From Sentences To Narrativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the functional architecture of this network-i.e., the division of linguistic labor among its constituent regions-remains highly debated. On the one hand, some neuroimaging studies have suggested that different linguistic processes are localized to focal and distinct subsets of this network (e.g., Stowe et al, 1998;Vandenberghe et al, 2002;Bornkessel et al, 2005;Humphries et al, 2006;Caplan et al, 2008;Snijders et al, 2009;Meltzer et al, 2010;Pallier et al, 2011;Brennan et al, 2012;Goucha and Friederici, 2015;Zhang and Pylkkänen, 2015;Kandylaki et al, 2016;Frank and Willems, 2017;Wilson et al, 2018;Bhattasali et al, 2019). On the other hand, other studies have reported that such processes are widely distributed and spatially overlapping (e.g., Keller et al, 2001;Vigneau et al, 2006;Fedorenko et al, 2012b;Bautista and Wilson, 2016;Blank et al, 2016;Fedorenko et al, 2018;Siegelman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%